2021
DOI: 10.1016/j.ijid.2021.01.071
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Imaging Features of Adults with Recurrent Pulmonary Tuberculosis - A Prospective Case-Controlled Study

Abstract: Background: Recurrent pulmonary tuberculosis (RPTB) is a growing, important and neglected problem affecting treated TB patients and TB health services across the world, particularly in sub-Saharan Africa. Analyses and identification of differences in clinical features between recurrent PTB and newly diagnosed PTB may lead to improved management recommendations. Methods: Between September 1 st 2019 and January 31 st 2020, we performed a prospective case controlled study of clinical and imaging features of patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 28 publications
(39 reference statements)
0
9
0
1
Order By: Relevance
“…This finding may apparently contradict other studies that have reported TBDM comorbidity to be associated with greater TB severity and a more severe clinical presentation of TB in individuals with TBDM compared to those with APTB alone [ 64 , 65 ]. However, we consider that this can be explained by the absence of relapse TB cases in the TBDM group, which generally predisposes patients to greater lung injury [ 66 ]. The fact that approximately 56% of individuals with TBDM had a good glycemic control at the start of standard TB treatment (A1c <7%), influenced mycobacterial load, improved metabolism, and enhanced immunity against the causative agent of TB in individuals with TBDM [ 67 - 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding may apparently contradict other studies that have reported TBDM comorbidity to be associated with greater TB severity and a more severe clinical presentation of TB in individuals with TBDM compared to those with APTB alone [ 64 , 65 ]. However, we consider that this can be explained by the absence of relapse TB cases in the TBDM group, which generally predisposes patients to greater lung injury [ 66 ]. The fact that approximately 56% of individuals with TBDM had a good glycemic control at the start of standard TB treatment (A1c <7%), influenced mycobacterial load, improved metabolism, and enhanced immunity against the causative agent of TB in individuals with TBDM [ 67 - 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to previously treated patients had a higher proportion of smear-positive cases or extensive cavitation on chest radiograph as compared to new patients [24], Increased duration of exposure of ATT in the past also increases the risk of the development of mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Meskipun penyembuhan mikrobiologis, setiap episode TB Paru (PTB) dikaitkan dengan ketakutan dan gejala sisa jangka panjang yang tidak sepenuhnya dan sistematis ditangani dengan pengobatan anti-tuberkulosis. (Nagu et al, 2021) Dengan demikian, episode PTB yang berulang menjadi predisposisi pasien untuk cedera paru lebih lanjut. Analisis dan identifikasi perbedaan fitur klinis antara kasus TB baru dan berulang dapat mengidentifikasi perbedaan mendasar yang dapat mengarah pada rekomendasi manajemen yang lebih baik…”
Section: Pendahuluanunclassified